Comprehensive study of heart rate recovery and altered ventilatory response to exercise in patients with obstructive sleep apnea - Layla Abdelhaleem Banawan; Rasha Galal Daabis; Hend Ramadan Atia Abdehaleim; Heba Ahmed Eshmawey (The Egyptian Journal of Bronchology)
Abstract Background Obstructive sleep apnea is a chronic disorder that results in many cardiovascular disorders including hypertension and arrhythmias. Cardiopulmonary exercise testing (CPXT) has been used for measuring VO2, VCO2, and VE. This may have clinical utility if added to polysomnography used to identify OSA. Aim of study To assess altered ventilatory response and heart rate recovery in response to exercise in patients with obstructive sleep apnea and their relation to its severity. Patients and methods Case control study was enrolled including 30 OSA patients divided into (5 mild, 8 moderate, and 17 severe) and 15 healthy control. The two groups underwent cardiopulmonary exercise testing and different parameters were calculated. Results Greater VE, VE/VCO2, VE/VO2 ratios, and VE/VCO2 slope were statistically significant regarding the patients group compared to control group (p < 0.001, F ¼ 69.053, 104.381, 140.806, and 68.010, respectively. OSA patients had a reduced maximal exercise capacity expressed as lower VO2 peak, decreased BR and VO2 at anaerobic threshold compared to control group (p < 0.001, F ¼ 22.597, 68.773, and 82.90, respectively). Delayed HRR and weaker CR in patients with OSA than in controls with negative relationship to severity of OSA were proved (p < 0.001, F ¼ 119.493 and 91.271, respectively). The study revealed elevated max SBP, max DBP, and recovery SBP in the following 2 min after exercise in patients with OSA relative to their healthy controls with positive relationship to the severity of OSA (p < 0.001, F ¼ 37.129, 169.275, and 244.609, respectively). Conclusion Patients with OSA demonstrated exaggerated ventilatory response to exercise and autonomic dysfunction.